Tripe palm: a paraneoplastic manifestation of carcinoma stomach - P., Arun; N., Gireesh G.; A., Jinsha K.; Jayaraj, Vani (International Journal of Research in Medical Sciences, 2019)
Usually gastrointestinal malignancies present with low SAAG ascites. But when there is diffuse liver infiltration following malignancy, high SAAG ascites can occur. So liver infiltration can masquerade as cirrhosis. Malignant acanthosis and tripe palm are the paraneoplastic manifestations seen in GI malignancies. We are reporting a case which was initially managed as a straightforward case of cirrhosis ,but later turned out to be a case with tripe palms, malignant acanthosis and carcinoma stomach as primary with diffuse liver infiltration having high SAAG ascites.